2016
DOI: 10.1097/mpa.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Fibrosis and Expression of Matricellular Proteins Correlate With Histological Grade of Intraductal Papillary Mucinous Neoplasm of the Pancreas

Abstract: ObjectiveThe aim of the study was to clarify the correlation between the microenvironmental factors and histological grade in intraductal papillary mucinous neoplasm (IPMN).MethodsWe investigated 65 IPMNs resected at Yamagata University Hospital between 2000 and 2011, and all cases were categorized to low-inter (including low- and intermediate-grade dysplasia) and high-inv (including high-grade dysplasia and IPMN with an associated invasive carcinoma) groups. We compared between the 2 groups pathologically wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…5.3.1A). PanIN-and IPMN-associated stroma has been identified with increasing fibrosis correlated with increasing grade (50,105). This observation suggests that PAK1 is involved in the stroma of pre-and established pancreatic cancers and could be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 87%
“…5.3.1A). PanIN-and IPMN-associated stroma has been identified with increasing fibrosis correlated with increasing grade (50,105). This observation suggests that PAK1 is involved in the stroma of pre-and established pancreatic cancers and could be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies reported that ST and the malignant transformation of IPMN were significantly related . ST represents interstitial fibrosis and is caused by several microenvironmental factors .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that ST and the malignant transformation of IPMN were significantly related. [31][32][33] ST represents interstitial fibrosis and is caused by several microenvironmental factors. [34][35][36] Shindo et al 37 found that podoplanin hyperexpression in the intramural regions of IPMN significantly affected cancer invasion and interstitial fibrosis and that the malignant transformation of IPMN correlated with ST. Based on these molecular pathological findings, we believe that although ST was an indirect finding, it was closely associated with the malignant transformation of IPMN.…”
Section: T He Present Study Investigated Whether St Mnmentioning
confidence: 99%
“…Pre-invasive lesions (i.e. PanIN 38 , MCN 39 or IPMN 40 ) in humans and mice [19][20][21][22][23][24][25] also induce PSC activation, either as a result of microscopic structural deformations and ductal obstruction (inducing injury and obstructive lobular atrophy) 41 or by direct paracrine signaling from transformed epithelia.…”
Section: Delineation Of Pda-associated Fibroblast Subtypes or Activatmentioning
confidence: 99%